General anesthesia for the dental care of children and people with disabilities - Liliana Esther García Rosales; Marisol Sánchez Molina; Yeis Miguel Borré Ortiz (Editorial Ciencias Médicas, 2022)
Introduction: General anesthesia is considered to be a pharmacological tool included among the advanced dental techniques used to manage uncooperative and physically and/or mentally disabled patients, as well as a support mechanism in the performance of dental treatments. Objective: Evaluate the use of general anesthesia for the dental care of children and people with disabilities. Methods: A systematic bibliographic review was conducted of 17 studies published from 2009 to 2019 in six databases: MedLine-PubMed, LILACS, SciELO, Clinical Key, IBECS and Cuiden. The study followed the recommendations contained in Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and maintained the corresponding ethical and methodological rigor. Results: Search results made it possible to characterize the studies by year, country and methodological approach. The evidence obtained shows that general anesthesia is useful and effective as a technique to control the behavior of children and people with disabilities during dental care. Conclusions: General anesthesia is an excellent alternative as a technique to solve the oral problems of children and people with physical and/or mental disabilities, thus improving their quality of life.